Detection of Malathion in Ipomoea aquatica Using a Plasmonic Sensor Based on Ag-Modified Gold Nanobipyramids - Iwantono, Iwantono; Morsin, Marlia; Yudani, Ananda Febri; Syajali, Hidayati; Ziliwu, Friska; Simbolon, Norsinta Ida; Nafisah, Suratun; Isda, Mayta Novaliza; Emrinaldi, Tengku (Green Engineering Society, 2025)
Malathion is an organophosphate pesticide commonly used in agriculture to protect various crops, including Ipomea aquatica. I. aquatica is a widely consumed vegetable that is vulnerable to pests, such as caterpillars, which damage its leaves. Malathion is an insecticide effective against caterpillars on Ipomoea aquatica without affecting its internal tissues. However, excessive use of this pesticide may leave residues that pose risks to the environment and human health. This study aims to develop a plasmonic sensor based on silver-modified gold nanobipyramids (Ag-GNBPs) for malathion detection. This plasmonic sensor employs anisotropic gold nanomaterials, specifically silver-coated gold nanobipyramids, to enhance localized surface plasmon resonance (LSPR) and improve detection sensitivity. Silver is used due to its high electrical conductivity and responsiveness to electrical and light stimuli. Ag-GNBPs were synthesized using the seed-mediated growth method, and their optical, structural, and morphological properties were characterized via UV-Vis spectroscopy, XRD, and FESEM. The UV-Vis absorption spectrum exhibited transverse (T-SPR) and longitudinal (L-SPR) surface plasmon resonance peaks at 500-600 nm and 700-900 nm, respectively. Testing involved adding the analyte to the solution and analyzing LSPR spectrum changes via UV-Vis spectroscopy. The observed LSPR peak shifts correlated with malathion concentration, with enhanced sensitivity due to silver modification. The results demonstrated that the plasmonic sensor based on silver-modified gold nanobipyramids not only detected malathion with high accuracy but also exhibited high sensitivity at low concentrations, which is essential for environmental monitoring and food safety applications. The optimal growth time for the seed-mediated growth method was 2 hours.